Persepsi Ibu Hamil tentang Penggunaan Alat Kontrasepsi Pasca Melahirkan di Klinik Dr. Sunedi Tahun 2024 - Sari, TaJunawalia Mayang; M, Maryam; Thaher, M. Iman Tarmizi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore pregnant women's perceptions regarding the use of postnatal contraception at Klinik Dr. Sunedi. A quantitative research design with a descriptive analytic approach was employed, involving 30 respondents selected via purposive sampling. Data were analyzed using univariate methods to describe demographic characteristics and respondents’ perceptions, as well as bivariate analysis to examine the relationships between demographic variables and the perception of postnatal contraception use. The findings indicate that most pregnant women hold a positive perception of the benefits of postnatal contraception, although some challenges related to knowledge and access to information were identified. These findings are expected to inform the development of educational programs and improvements in reproductive health services at the clinic.